THUR 158 Susac's syndrome: treatment and outcomes in three cases. Issue 10 (13th September 2018) - Xin, Chua Wei; Dan, Whittam; Saif, Huda; David, Rog; Martin, Wilson; David, Smith; Peter, Enevoldson; Anu, Jacob
Abstract : Background: Susac's syndrome (SS) is a rare, autoimmune microangiopathy causing a triad of branch retinal artery occlusions, sensorineural hearing loss and brain lesions. Published data on immunotherapy and outcomes is very limited. Method: Single centre case note review. Electronic hospital records between 1996 and 2017 were searched. 277 possible cases were reviewed. Results: 3 cases (2 female, 1 male) with the full SS triad were identified. Median age of disease onset was 35.2 years with headache (n=3), confusion (n=1), hearing loss (n=3), vertigo (n=2) and visual field loss (n=2). Time from onset to diagnosis with the full triad was 3–23 months. MRIs showed characteristic corpus callosum involvement. All patients received high-dose corticosteroids as acute therapy. Case 1 was treated with Mycophenolate Mofetil (MMF) and Prednisolone for 27 months, and followed up for a further 8 months. She remained relapse-free. Case 2 relapsed on steroid-reduction, so received Rituximab followed by MMF and Prednisolone. She has now been stable for 14 months. Case 3 was intolerant to high-dose corticosteroids, Cyclophoshamide and MMF. He relapsed off treatment then commenced Azathioprine. Duration on Azathioprine is 14 months with one further relapse. Conclusion: SS is rare but causes significant morbidity. Recognition of characteristic findings and early immunotherapy improves outcomes.